The Determinants of Profit-Sharing Rates for Mudharabah Deposits: The Case of Islamic Banks in Indonesia - Kautsar Riza Salman (Türkiye İslam İktisadı Dergisi)
Collecting Islamic bank funds with mudharabah contracts, such as mudharabah deposits, will offer depositors a profit-sharing rate. This study aims to obtain empirical evidence regarding the deter- minants of the profit-sharing rate for mudharabah deposits. The determinants in this study are non-per- forming financing, operational efficiency, capital adequacy, and third-party funds. The sample used in this study was 11 Islamic commercial banks in Indonesia from 2015-2019. The results show that only capital adequacy affects the profit-sharing rate for mudharabah deposits. The increase in the capital adequacy ra- tio of Islamic banks in the study period significantly impacted the decrease in the rate of profit-sharing on deposits received by third parties, especially from 2017 to 2018. The results also show that non-perform- ing financing, operational efficiency, and third-party funds do not affect profit-sharing deposits. Problem financing and operational efficiency are still the main problems Islamic banks face in Indonesia, so they do not impact the profit-sharing rate for mudharabah deposits. Third-party funds also tend to decrease during the study period so that it does not impact the profit-sharing rate for mudharabah deposits. The study’s findings are expected to generate theoretical contributions to scientific development in concepts and empirical research in the Islamic banking sector, practical contributions to Islamic banks in their op- erational activities, and policy contributions to regulators in setting policies in the Islamic banking sector.